Caracterização estrutural do polissacarídeo sulfatado da alga marinha Bryothamnion seaforthii: efeito antioxidante e toxicidade - Chagas, Francisco Diego da Silva (2022)
Oxidative stress is a biochemical condition of imbalance that can culminate in the degradation of cellular structures and trigger numerous pathologies. From this perspective, marine seaweed carbohydrates are presented as alternative macromolecules capable of combating oxidative stress, due to the antioxidant potential already described in the literature. Therefore, the study aimed to isolate, characterize, evaluate toxicity and antioxidant effect of the sulfated polysaccharide from Bryothamnion seaforthii. The red seaweed B. seaforthii was collected at Praia de Guajiru (Trairi, Ceará) and subjected to proximate composition analysis. After the first step, the sulfated polysaccharide of Bryothamnion seaforthii (SP-Bs) was obtained by enzymatic digestion, which was subjected to chemical characterization through colorimetric analysis, elemental microanalysis, Scanning Electron Microscopy (SEM), Gel Permeation Chromatography (GPC), Fourier Transform Infrared Spectrometry (FTIR) and Nuclear Magnetic Resonance (NMR). The toxicity of SP-Bs was evaluated against Artemia sp. and in BALB/c mice and its antioxidant effect against different radicals was investigated. The macroalgae B. seaforthii showed high carbohydrate content (75.05 ± 0.21%) and SP-Bs showed 91.4% of total carbohydrates and only traces of protein contaminants (<1%). Furthermore, it presented laminated morphology with short branched chains verified by SEM. GPC and elemental microanalysis techniques revealed that SP-Bs have an average molar mass of 74.4 kDa and a degree of sulfation of 0.67, respectively. Furthermore, FT-IR and NMR confirmed that PS-Bs is an agaran-type galactan. SP-Bs showed no toxic effect in any of the tests and did not promote significant changes in clinical, biochemical and histological parameters in mice. SP-Bs exhibited concentration-dependent antioxidant effect in the test that investigates total antioxidant capacity (2.48-98.64%), ferrous ion chelation (5.73-54.05%) and hydroxyl radical scavenging (13.79-72.27%). These results suggest that SP-Bs is a promising natural antioxidant that has no toxic effects.